Developing geospatial thinking learning lines in secondary education: The GI learner project - Luc ZWARTJES (European Journal of Geography)
Geo-ICT is part of the digital economy identified by the European Commission as being vital for innovation, growth, jobs and European competitiveness. It is a rapidly growing business sector, but it is in many countries a shortage occupation sector. More attention to Geo-ICT in education, which relates to geospatial thinking, would help. The GI Learner project developed therefore a geospatial thinking learning line for secondary schools, so that integration of geospatial thinking can take place. The learning line concept used hereby different levels of complexity, referring to the taxonomy of Bloom, taking into account age and capabilities of students. For each of the competencies lesson materials related to the curriculum was produced, thus facilitating the implementation in education on short term. To measure the impact of the learning lines on spatial thinking a self-test was therefore developed, taking into account the level of complexity of each competence (A, B or C) for each age group. The GI Learner project website (http://www.gilearner.eu) provides access to as well the research publications as well as the developed teaching resources.